2019
DOI: 10.1002/jcsm.12485
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pulmonary function and physical performance among community‐living people: results from Look‐up 7+ study

Abstract: Background While respiratory muscle strength is recognized to decline with aging process, the relationship between sarcopenia and pulmonary function remains to be studied. The present study was undertaken to provide a better insight into the comprehension of the relationship between pulmonary function and muscle function (strength and physical performance) using an unselected sample of subjects assessed during the Longevity Check‐up 7+ project. Methods Look‐up 7+ is an ongoing cross‐sectional survey started in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In older people, low inspiratory muscle endurance is associated with the low walking performance ( 27 ). The time taken to perform a task in chair stand tests shows a positive correlation with FVC, FEV1, and peak expiratory flow (PEF) ( 39 ). Physical performance, balance, and gait scores in low PEF group were significantly lower compared to a normal PEF group ( 40 ).…”
Section: Age-related Respiratory Sarcopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…In older people, low inspiratory muscle endurance is associated with the low walking performance ( 27 ). The time taken to perform a task in chair stand tests shows a positive correlation with FVC, FEV1, and peak expiratory flow (PEF) ( 39 ). Physical performance, balance, and gait scores in low PEF group were significantly lower compared to a normal PEF group ( 40 ).…”
Section: Age-related Respiratory Sarcopeniamentioning
confidence: 99%
“…Vital capacity and FVC are common measurement methods for respiratory function. We adopted FVC as a measure of respiratory function, as FVC is associated with sarcopenia ( 39 , 70 ). As with MIP, FVC varies by body size, so it is considered adaptable to local standards ( 21 ).…”
Section: Diagnosis Of Respiratory Sarcopenia and Sarcopenic Respiratomentioning
confidence: 99%
“…The time taken to complete the task(s) was measured using a handheld stopwatch and was used for the analyses. 17,18…”
Section: Muscle Strength Testingmentioning
confidence: 99%
“…We focused on SMI alone, which is a biomarker of sarcopenia. A previous study has reported the relationship between pulmonary function and physical performance 28) . Second, it was difficult to establish the exclusion criteria for older adults who had various comorbid diseases and a complex medical history.…”
Section: Discussionmentioning
confidence: 99%